Greece Reinvented: Shakespeare’s “Greek Plays” as a Subgenre - Yarong, Wu; Tianhu, Hao (Multicultural Shakespeare: Translation, Appropriation and Performance, 2024)
This article justifies the addition of “Greek Plays” as a subgenre to classify Shakespeare’s works. The six plays (A Midsummer Night’s Dream, Timon of Athens, Two Noble Kinsmen, The Comedy of Errors, Pericles, Prince of Tyre, and Troilus and Cressida) in this subgenre are defined as adaptations of ancient Greek literature, staged in Greek or closely related settings, and featuring characters from Greek mythology and history. Through a review of the research history of Shakespeare’s Greek plays and an exploration of interactions between Englishmen and Greeks, the authors provide a brief but comprehensive reading of his Greek plays and argue that Shakespeare juxtaposes ancient Greece with its early modern counterpart—a territory of difference and the Other—on the very edge of Europe, penetrated by the alien East and Islamic cultures. Greece is a land of ambiguity, reinvented by Shakespeare as a liminal space, and characterized by a mixture of humanist admiration for the grandeur of ancient Greek civilization, cautious respect for and alertness to its pagan origins, a profound desire for economic benefits in the Eastern Mediterranean, and Christian apprehensions and anxieties in Englishmen’s encounters with the Turks. By introducing “Greek Plays” as a subgenre, this paper not only helps to enrich our understanding of Shakespeare’s portrayal of “a world elsewhere” from multifaceted cultural perspectives but also attempts to expand the existing territory of Shakespearean studies.